Roles of Telomeres and Telomerase in Aging - Khing S. Ong; Zack S.T. Liem; Boenjamin Setiawan (PT Kalbe Farma Tbk., 2019)
Telomeres are DNA structure that capped the end of linear eukaryotic chromosomes to protect the stability and integrity of the chromosomes. Attrition of telomeres has been known as one of the hallmark of aging. This review leads to huge interest in the biology of telomeres and the related enzyme in the aging and related fields. We attempt to review briefly the biology and functions of telomeres, factors, and mechanisms that control its length and its maintenance. Genetic and epigenetic related dysfunction of telomeres and telomerase will also be discussed. Finally, a list of disorders of telomeres and telomerase (telomeropathies) will be mentioned with potential therapeutic interventions for these disorders, and the potential for delaying cell senescence and health-span extension. Telomeres adalah bagian dari struktur DNA di ujung linier helix eukaryotic chromosome sebagai penutup/cap untuk menghindari dan melindungi bagian ujung kromosom dari kerusakan dan untuk menjaga kestabilannya. Telomeres akan mengalami erosi atau pemendekan yang merupakan tanda penuaan/aging. Proses ini mendapat perhatian besar sehubungan dengan peristiwa penuaan. Ulasan singkat ini tentang sifat-sifat biologi dan fungsi telomeres. Akan dibahas pula akibat pergeseran/disfungsi genetik dan epigenetik yang menyebabkan perubahan telomeres dan telomerase. Di akhir pembahasan, dicantumkan daftar telomeres dan telomerase (telomeropathies) yang dapat diintervensi dan dapat memperlambat proses penuaan, dengan kata lain memperpanjang usia.